Gerattak Semate: Syncretism Representation of Sambas Malay Timang Bubu’s Folkgame - Rama Anggara; Asril (Universitas Negeri Medan, 2026)
Gerattak Semate is a representation of the syncretism of the Sambas Malay Timang Bubu folkgame in music composition. Timang Bubu is a folkgame that grows and develops in Semate Village, Sambas Regency. The folkgame uses bubu / a type of fishing tool made of bamboo. The phenomenon in the folkgame is used as a stimulus as the material object of creation. The syncretism element contained in it is used as a trigger for the idea of creating musical works. The work of Gerattak Semate is worked on in four works that are mutually sustainable. The four works were created using interpretation and reinterpretation approaches. Interpretation is aimed at interpreting and synthesizing the meaning and socio-cultural values contained in the phenomenon of the Timang Bubu’s folkgame. Reinterpretation is applied to the utilization and development of musical elements in the Timang Bubu’s folkgame as well as the pattern of traditional Malay music that grows and develops in West Kalimantan. Gerattak Semate is composed by applying a combination of hybrid instrumentation. This is done by mixing traditional Malay musical styles and instruments, western instruments, and electronic media. The mixture of various musical idioms and expressions used as a representation of syncretism. Subjectively, this work was conceived as a bridge to present socio-cultural values with a pluralistic frame of mind.